Ligand‐Free and Reusable Palladium Nanoparticles‐Catalyzed Alkylation of 2‐Alkylazaarenes with Activated Ketones under Neutral Conditions. Issue 18 (25th July 2019) - Parveen, Naziya; Muthukumar, Alagesan; Sekar, Govindasamy
Abstract: A mild, efficient, and stable binaphthyl‐stabilized palladium nanoparticles (Pd−BNP) catalyzed ( sp 3 )C−H reaction of 2‐alkylazaarenes with activated carbonyl compounds was developed. Various activated carbonyl compounds such as α‐keto amide, isatin, 1, 2‐diketone, α‐keto ester, trifluoromethyl ketone, and phenylglyoxal derivatives were examined and most of the compounds underwent the reaction smoothly to provide the corresponding products in moderate to excellent yields. Moreover, chemoselective reactions of α‐keto amides in the presence of simple ketones were achieved. Also, the model reaction was extended to a gram‐scale synthesis and some of the products were utilized for derivatization to form the corresponding N ‐oxides, acryl amides and 1, 2‐diol, respectively. The major advantages of the protocol are neutral reaction conditions, no additional requirement of external ligand, and successful reusability of the Pd−BNP catalyst up to five cycles without losing its activity and yield. Hg‐poisoning and hot filtration tests confirmed the heterogeneity of the Pd−BNP catalyst. Abstract :